Molybdenum and nickel foliar application on soybean yield and oil and protein contents - Moreira, Adônis; Cardoso, Bruna Miguel; Dameto, Larissa Sartori; Delfim, Jorge [UNESP]; Moraes, Larissa Alexandra Cardoso; Lazarini, Edson [UNESP] (FapUNIFESP (SciELO), 2024)
The objective of this work was to evaluate the effect of the foliar application of molybdenum (Mo) and nickel (Ni) on the grain yield, yield components, and oil and protein contents in the grains of soybean cultivated under two edaphoclimatic conditions in Brazil. The following soybean genotypes were evaluated at the beginning of the R1–R2 growth stage: 'Brasmax Desafio RR', in the municipality of Londrina, in the state of Paraná; and 'TMG 7063 IPRO' and 'Brasmax Desafio RR', in the municipality of Selvíria, in the state of Mato Grosso do Sul. The treatments consisted in the application of four Mo rates (0, 400, 800, and 1,600 g ha-1) and three Ni rates (0, 60, and 120 g ha-1). The soybean genotypes exhibited varying responses to the two edaphoclimatic conditions. The foliar application of Mo is an effective strategy to increase the grain yield and protein content of 'TMG 7063 IPRO' e 'Brasmax Desafio RR'. However, with the application of 120 g ha-1 Ni, both genotypes show the worst performance for yield components and oil and protein contents. The 'Brasmax Desafio RR' genotype presents varied responses across different soil and climate conditions.
Aplicação foliar de molibdênio e níquel na produção de soja e nos seus teores de óleo e proteína
Keywords: Glycine max; grain quality; micronutrients